Aromatic plants from Patagonia. Part I. Antimicrobial activity and chemical composition of Schinus polygamus (Cav.) Cabrera essential oil - González, Silvia (2004)
The essential oil of Schinus polygamus (Cav.) Cabrera f: chubutensis (syn. S. marchandii Barkley) was analysed for the first time by means of GC and GC-MS. Of 30 identified compounds, representing 96.3% of the oil, α-phellandrene and limonene were the major components. The oil showed high antimicrobial activity against B. cereus.